Investment feasibility and marketing of mangosteen commodity in Central Sulawesi, Indonesia - Marianne Reynelda Mamondol (Publisher of Widyagama University of Malang (UWG Press), 2020)
The development of mangosteen agribusiness in the regions needs attention to benefit local economic development. This research aims to analyze the investment and marketing feasibilities of mangosteen commodity at Olumokunde Village, Poso Regency, Central Sulawesi, Indonesia. Research respondents, as many as 60 farmers, were determined through stratified sampling technique. Data collection was done through observations, interviews, questionnaires to respondents, and documentary study. Research results demonstrate that mangosteen farms meet investment feasibility. The research found that the indicator of net present value was 87.496 million rupiahs, the internal rate of return was 19.8% and the payback period was 10.95 years. Since its 7th year, the mangosteen farm business’ amount of revenue has been higher than its operational costs. Also, the research reveals farm sensitivity on the changes of cost production, selling price, and mangosteen production. There are two models of mangosteen fruit marketing channel at Olumokunde: (i) direct marketing from farmers to consumers, and (ii) indirect marketing through fruit wholesalers. The mangosteen agribusiness development needs regional government intervention in the forms of facility and infrastructure requirement as well as supply chain strengthening in order to create large-scale, economical, and highly competitive farms.JEL Classification D25; O22; Q13